Distribution of artifacts and ecofacts in an Early Bronze Age house in Eastern Anatolia: Space use and household economy at Arslantepe VI B2 (2900–2750 BCE). (December 2015) - Piccione, Paola; Alvaro, Corrado; Bartosiewicz, Laszlo; Lemorini, Cristina; Masi, Alessia; Sadori, Laura
Abstract: Arslantepe, one of the best documented mounds in Eastern Anatolia, is well known especially for its Late Chalcolithic 'palace', testifying to the emergence of a centralized and redistributive economy, typical in the 4th millennium BCE Uruk and Uruk-related worlds. At the beginning of the Early Bronze Age this socio-economic system undergoes a collapse, and the degree of control of the economy on behalf of the 'elites' seems to be, here and in other sites, significantly lower or even non-existent. This topic (in need of further investigation) may be enriched by studies focusing on the household level and aimed at assessing the role of household economy. By applying a multidisciplinary approach, this research combines zoological, botanical and artifactual evidence from a multi-roomed mud-brick dwelling in the Early Bronze Age settlement of Arslantepe — VI B2 (2900–2750 BCE), which was destroyed by a fire and suddenly abandoned: an event entailing the retrieval of a very rich assemblage of in situ ecofacts and artifacts. In this paper we present in detail the carpological, anthracological and archaeozoological finds and – after describing the architectural layout of the house under examination – we assess the morpho-functional characteristics of both ceramics and lithics (the latter determined through use-wear analysis) and examine the spatial and stratigraphic patterning of all the materials: although partly biased by taphonomic modifications, the sub-assemblages of the different indoor and outdoor spaces of the examined dwelling reflect the functional characteristics of each area. Additionally, we combine our results with preliminary data from other parts of the extensively excavated village of period VI B2, pointing out the prominent role of household economy in this phase. Highlights: Spatial and stratigraphic patterning of materials in an EBA I house at Arslantepe, TK Zoological (NISP, age patterns, anatomical distributions) and botanical analyses Outcomes are combined with morpho-functional study of artifacts (including lithic use-wear). Functional definition of different parts of the house and detection of taphonomic biases Results (combined with preliminary data on other houses) suggest a major role of household economy in this phase.